Onein : Pendidikan Multikulturalisme Berbasis Akun Instagram yang Praktis dan Menarik Menuju Indonesia Emas 2045 - Fajar Harry Akbar; Eva Agus Triana; Ghiffari Faizi Ramadhan (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
This research is motivated by the author's observations and several previous studies regarding the issue of identity politics, multiculturalism and radicalism. The 2017 DKI Pilkada became an event that attracted attention because of the issue of identity politics in it. The number of access to social media in the country is one of the highest in the world. It makes up most of our time on social media. The issue of identity politics is also rife on social media. This becomes extreme when there is hate speech between groups and even causes radicalism. The method used is descriptive qualitative sourced from primary and secondary data with data analysis techniques to analyze the educational needs of multiculturalism. Based on these conditions, the author initiated an innovation in the form of OneIn, namely an Instagram account that provides multiculturalism education with interesting and practical delivery.